(untitled) (Bangladesh Journal of Medical Science, 2024)
Objective Nursing care is a unique and indispensable concept for nursing that includes helping to meet the needs of an individual or a group of individuals offered by nurses. This study is aimed to test the validity and reliability of the Turkish version of the Quality Nursing Care Scale (QNCS-T). Materials and Methods The methodological approach employed in this study spanned from April 25, 2021, to May 5, 2021, and enlisted the participation of 347 nurses. Data collection was executed utilizing a “Personal Information Form” and the “Quality Nursing Care Scale (QNCS).” The research comprised two phases: Phase 1 involved the adaptation of the scale, while Phase 2 focused on determining construct validity through confirmatory factor analysis. Reliability was assessed through measures of internal consistency and item-total correlation coefficients. Results and Discussion The adaptation phase yielded affirmative outcomes, affirming the linguistic and content validation of the Turkish version of the scale. Confirmatory factor analysis demonstrated a highly favorable fit for a sixfactor model. The Cronbach’s alpha coefficient for the entire scale was determined to be 0.93, attesting to its strong internal consistency. Conclusion The Turkish version of the Quality Nursing Scale showed consistently good psychometric properties of reliability and validity. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1075-1082